2021
DOI: 10.1371/journal.pone.0248759
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of elevated air temperature and drought on pollen characteristics of major agricultural grass species

Abstract: Grass pollen allergens are known to be one of the major triggers of hay fever with an increasing number of humans affected by pollen associated health impacts. Climate change characterized by increasing air temperature and more frequent drought periods might affect plant development and pollen characteristics. In this study a one-year (2017) field experiment was conducted in Bavaria, Germany, simulating drought by excluding rain and elevated air temperature by installing a heating system to investigate their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…The temperature difference in the two regions can have a possible effect on the FTIR spectra of the pollen samples. Increase in temperature and drought has been found to affect pollen weight, protein content and allergen contents [42]. In our studies, inter–regional and inter–seasonal pollens studied through Principal Component Analysis (PCA) showed significant differences in the FTIR datasets of pollens, which also confirmed differences in pollens chemical composition.…”
Section: Discussionsupporting
confidence: 79%
“…The temperature difference in the two regions can have a possible effect on the FTIR spectra of the pollen samples. Increase in temperature and drought has been found to affect pollen weight, protein content and allergen contents [42]. In our studies, inter–regional and inter–seasonal pollens studied through Principal Component Analysis (PCA) showed significant differences in the FTIR datasets of pollens, which also confirmed differences in pollens chemical composition.…”
Section: Discussionsupporting
confidence: 79%
“…Such dry conditions have been shown to reduce grass growth and pollen production (González Minero et al, 1998), thus accounting for the lack of correlation between Poaceae pollen and temperature and the negative correlation between total pollen and temperature during June 2018 (Dublin). Many grass species are dependent on precipitation and have a low tolerance to drought (Jung et al, 2021), explaining the positive correlation observed between Poaceae pollen and rainfall in Carlow 2018.…”
Section: Discussionmentioning
confidence: 99%
“…This community is able to provide informed grass pollen warnings to the public by collating information from a wide range of sources, including but not limited to grass pollen monitoring datasets, grass pollen trend analyses (Emberlin et al, 1999;, local grass flowering observations (Frisk et al, 2021;León-Ruiz et al, 2011), grass maps (McInnes et al, 2017), current weather conditions and climatic trends. Previous studies are generally in agreement that temperature, precipitation, and local grass areas are important factors in this dynamic (García-Mozo et al, 2010Jung et al, 2021;Recio et al, 2010;Ščevková et al, 2020;Skjøth et al, 2013;Werchan et al, 2017). This is due both to the growth and maturity of the plants (Charles-Edwards et al, 1971;Förster et al, 2018;Hurtado-Uria et al, 2013) but also the impact on flowering and the release of pollen (Cebrino et al, 2016;Emecz, 1962;Romero-Morte et al, 2020).…”
Section: Introductionmentioning
confidence: 53%
“…The effect has been shown to have a measurable effect on grass pollen levels in the atmosphere (Ríos et al, 2016). A possible reason for the strong significant effect of temperature on grass pollen levels is not only due to the direct (although complicated) effect (Jung et al, 2021;Myszkowska, 2014;Norris-Hill, 1997), but also from the indirect effect mediated through plant growth, plant maturity, anthesis and anther dehiscence (Charles-Edwards et al, 1971;Liem and Groot, 1973). All of the factors mentioned have their own complex relationships to grass pollen release and atmospheric concentrations (Viner et al, 2010).…”
Section: Transportation Distance and Meteorologymentioning
confidence: 99%